RESPONSE AND PERFORMANCE OF MAIZE (Zea mays) TO SOIL AMENDMENT IN ASABA, DELTA STATE, NIGERIA (FULafia Journal of Science and Technology, 2019)
Response of maize to soil amendment was carried out in degraded oxisol of Asaba, Delta State Nigeria using early OBA super 2 hybrid maize. This was planted in July and harvested in September during the 2016 and 2017 cropping seasons at the Agronomy Teaching and Research Farm, Delta State University, Asaba Campus. Four levels of poultry droppings and 200 kg-1 of NPK 20:10:10 were applied in a randomized complete block design (RCBD) and, replicated three times. Growth parameters assessed were plant height, leaf area and plant girth while stover, weight of 1000 grains and grain yield were measured at harvest. Soil chemical properties were determined during the second season harvest. Data was subjected to analysis of variance and means were separated with Duncan’s Multiple Range Test (DMRT) at 5% level of probability using the …(name of software used). Results showed that NPK 20:10:10 had the best in first season but second season, poultry droppings at 10.0 t ha-1 had the best and was significantly higher than NPK 20:10:10 in leaf area, plant girth and stover yield but not significantly higher in plant height,1000 grains weight and grain yield. This further improved the potential of poultry droppings for sustainable production than NPK 20:10:10. The study confirmed that poultry droppings could be an alternative source of plant nutrients on sustainable production bases on degraded acidic oxisols.
Keywords: alternative to mineral fertilizer; soil amendment; soil fertility; maize and organic waste